Complejo de educación superior para el desarrollo agroindustrial - Dehesa: Plan parcial sabana vital Mosquera - Cundinamarca (2017)
It is proposed the design of the Higher Education Complex for the agro industrial development in Mosquera, Cundinamarca, from the regional analysis to the province Sabana de Occidente where there is a strong agricultural potential with certain problems to solve and a clear positioning of the industry Thanks to the strategic geographical location. The document covers all the analysis and diagnosis of the region and the integral proposal of architectural design.